Defining the Role of Polyphosphate in the Bacterial Stress Response - Baijal, Kanchi (Université d'Ottawa / University of Ottawa, 2025)
Polyphosphates (polyP) are chains of phosphate residues that are joined together by high energy bonds. In bacteria, the role of polyP is implicated in the stress response. By comparison of wildtype (WT) to ppk mutant (Δppk) E. coli, the role of polyP has been tied to processes aimed to help bacteria adapt to stress. However, the underlying PPK-dependent pathways involved in promoting these processes remain unclear. To identify the broader role of polyP during bacterial stress, I conducted proteomics analysis of E. coli exposed to nutrient deprivation. I found 92 proteins significantly differentially expressed between wild-type and ∆ppk mutant cells. Wild-type cells were enriched for proteins related to amino acid biosynthesis and transport, while Δppk mutants were enriched for proteins related to translation and ribosome biogenesis, suggesting that without PPK, cells remain inappropriately primed for growth even in the absence of the required building blocks. Furthermore, from the dataset I followed up on Arn and EptA proteins which are downregulated in Δppk mutants compared to WT controls, because they play a role in lipid A modifications linked to polymyxin resistance. I provided evidence that mis-regulation in ∆ppk cells stems from a failure to induce the BasRS two-component system and showed that loss of ppk restores polymyxin sensitivity in resistant strains. Furthermore, I confirmed PPK-dependent regulation of the Bas-Arn circuit in uropathogenic E. coli. To better understand how polyphosphate (polyP) regulates protein function, I performed a screen to identify polyP-binding proteins in E. coli. This led to the discovery of 7 novel targets linked to ribosome biogenesis and translation control. For two of these targets - YihI and the ribonuclease Rnr - I mapped the interaction sites to non-PASK sequences within each protein and identified critical lysine residues involved in binding. Deletion of ppk resulted in reduced expression of Rnr, an exoribonuclease known to degrade mRNA and rRNA under stress and participate in trans-translation. In contrast, deleting rnr alleviated the slow growth phenotype observed in ppk mutants grown on MOPS minimal media. These phenotypic changes seem to depend on the polyP-binding region of Rnr, yet are independent of polyP binding itself, suggesting a complex interaction between PPK and Rnr in E. coli. Overall, this work expands our understanding of polyP-binding proteins in E. coli. Together, these works emphasize the pathways by which polyP and PPK promote bacterial adaptation and survival. Further, they uncover PPK and polyP-binding proteins as novel targets to manipulate bacterial fitness.
Keywords: Polyphosphate; polyP; polyP-protein binding; polymyxin resistance; Arn; EptA; BasRS; two-component systems; bacterial stress; stringent response